The Cultural Paradigm of Virtue - Crockett, Carter (Journal of business ethics, 2005)
Social and moral issues in business have drawn attention to a gap between theory and practice and fueled the search for a reconciling perspective. Finding and establishing an alternative remains a critical initiative, but a daunting one. In what follows, the assumptions of two prominent contenders are considered before introducing a third in the form of Aristotle’s ancient theory of virtue. Comparative case studies are used to briefly illustrate the practical implications of each paradigm. In the quest for a better sense-making and sense-giving lens, this paper refines and encourages the search by highlighting some of the key features required of a worthy paradigmatic challenge. The author proceeds to identify a particular type of institutional community, and a promising champion, for the practical unification of strategic and normative excellence.